Bioremediation of wastewater from edible oil refinery factory using oleaginous microalga Desmodesmus sp. S1. Issue 12 (1st December 2016) - Mar, Cho Cho; Fan, Yong; Li, Fu-Li; Hu, Guang-Rong
ABSTRACT: Edible oil industry produced massive wastewater, which requires extensive treatment to remove pungent smell, high phosphate, carbon oxygen demand (COD), and metal ions prior to discharge. Traditional anaerobic and aerobic digestion could mainly reduce COD of the wastewater from oil refinery factories (WEORF). In this study, a robust oleaginous microalga Desmodesmus sp. S1 was adapted to grow in WEORF. The biomass and lipid content of Desmodesmus sp. S1 cultivated in the WEORF supplemented with sodium nitrate were 5.62 g·L −1 and 14.49%, whereas those in the WEORF without adding nitrate were 2.98 g·L −1 and 21.95%. More than 82% of the COD and 53% of total phosphorous were removed by Desmodesmus sp. S1. In addition, metal ions, including ferric, aluminum, manganese and zinc were also diminished significantly in the WEORF after microalgal growth, and pungent smell vanished as well. In comparison with the cells grown in BG-11 medium, the cilia-like bulges and wrinkles on the cell surface of Desmodesmus sp. S1 grown in WEORF became out of order, and more polyunsaturated fatty acids were detected due to stress derived from the wastewater. The study suggests that growing microalgae in WEORF can be applied for the dual roles of nutrient removal and biofuel feedstock production.